A new corrective technique for adolescent idiopathic scoliosis (Ucar's convex rod rotation) - Uçar, Bekir Yavuz (Medknow Publications & Media Pvt Ltd, 2014)
STUDY DESIGN: Prospective single-center study. OBJECTIVE: To analyze the efficacy and safety of a new technique of global vertebral correction with convex rod rotation performed on the patients with adolescent idiopathic scoliosis. SUMMARY OF BACKGROUND DATA: Surgical goal is to obtain an optimal curve correction in scoliosis surgery. There are various correction techniques. This report describes a new technique of global vertebral correction with convex rod rotation. MATERIALS AND METHODS: A total of 12 consecutive patients with Lenke type I adolescent idiopathic scoliosis and managed by convex rod rotation technique between years 2012 and 2013 having more than 1 year follow-up were included. Mean age was 14.5 (range = 13-17 years) years at the time of operation. The hospital charts were reviewed for demographic data. Measurements of curve magnitude and balance were made on 36-inch standing anteroposterior and lateral radiographs taken before surgery and at most recent follow up to assess deformity correction, spinal balance, and complications related to the instrumentation. RESULTS: Preoperative coronal plane major curve of 62° (range = 50°-72°) with flexibility of less than 30% was corrected to 11.5°(range = 10°-14°) showing a 81% scoliosis correction at the final follow-up. Coronal imbalance was improved 72% at the most recent follow-up assessment. No complications were found. CONCLUSION: The new technique of global vertebral correction with Ucar's convex rod rotation is an effective technique. This method is a vertebral rotation procedure from convex side and it allows to put screws easily to the concave side.